A high speed model-based approach for wavefront sensorless adaptive optics systems. (1st February 2018) - Lianghua, Wen; Yang, Ping; Shuai, Wang; Wenjing, Liu; Shanqiu, Chen; Xu, Bing
Highlights: Reconstruct mode to complete synchronous mode correction in series one-by-one. The convergence becomes faster for the large aberrations by gradually correction. The fixed delay is more suitable for varied aberration corrections. Transforms the vector computations for modes coefficients to scalar for realtime. The simulated equivalent control bandwidth is 2–3 times than that of the previous. Abstract: To improve temporal-frequency property of wavefront sensorless adaptive optics (AO) systems, a fast general model-based aberration correction algorithm is presented. The fast general model-based approach is based on the approximately linear relation between the mean square of the aberration gradients and the second moment of far-field intensity distribution. The presented model-based method is capable of completing a mode aberration effective correction just applying one disturbing onto the deformable mirror(one correction by one disturbing), which is reconstructed by the singular value decomposing the correlation matrix of the Zernike functions' gradients. Numerical simulations of AO corrections under the various random and dynamic aberrations are implemented. The simulation results indicate that the equivalent control bandwidth is 2–3 times than that of the previous method with one aberration correction after applying N times disturbing onto the deformable mirror (one correction by N disturbing).